The proteome of bacterial membrane vesicles in Escherichia coli—a time course comparison study in two different media - Yu, Mia S. C.; Chiang, Dapi Menglin; Reithmair, Marlene; Meidert, Agnes; Brandes, Florian; Schelling, Gustav; Ludwig, Christina; Meng, Chen; Kirchner, Benedikt; Zenner, Christian; Muller, Laurent; Pfaffl, Michael W. (Frontiers in Microbiology, 2024)
Introduction Bacteria inhabit the in- and outside of the human body, such as skin, gut or the oral cavity where they play an innoxious, beneficial or even pathogenic role. It is well known that bacteria can secrete membrane vesicles (MVs) like eukaryotic cells with extracellular vesicles (EVs). Several studies indicate that bacterial membrane vesicles (bMVs) play a crucial role in microbiome-host interactions. However, the composition of such bMVs and their functionality under different culture conditions are still largely unknown. Methods To gain a better insight into bMVs, we investigated the composition and functionality of E. coli (DSM 105380) bMVs from the culture media Lysogeny broth (LB) and RPMI 1640 throughout the different phases of growth (lag-, log- and stationary-phase). bMVs from three time points (8 h, 54 h, and 168 h) and two media (LB and RPMI 1640) were isolated by ultracentrifugation and analyzed using nanoparticle tracking analysis (NTA), cryogenic electron microscopy (Cryo-EM), conventional transmission electron microscopy (TEM) and mass spectrometry-based proteomics (LC–MS/MS). Furthermore, we examined pro-inflammatory cytokines IL-1β and IL-8 in the human monocyte cell line THP-1 upon bMV treatment. Results Particle numbers increased with inoculation periods. The bMV morphologies in Cryo-EM/TEM were similar at each time point and condition. Using proteomics, we identified 140 proteins, such as the common bMV markers OmpA and GroEL, present in bMVs isolated from both media and at all time points. Additionally, we were able to detect growth-condition-specific proteins. Treatment of THP-1 cells with bMVs of all six groups lead to significantly high IL-1β and IL-8 expressions. Conclusion Our study showed that the choice of medium and the duration of culturing significantly influence both E. coli bMV numbers and protein composition. Our TEM/Cryo-EM results demonstrated the presence of intact E. coli bMVs. Common E. coli proteins, including OmpA, GroEL, and ribosome proteins, can consistently be identified across all six tested growth conditions. Furthermore, our functional assays imply that bMVs isolated from the six groups retain their function and result in comparable cytokine induction.